Integrierte Stadtentwicklung und die Gestaltung nachhaltiger Mobilität – Zum Stand der Planungspraxis am Beispiel der Stadt Leipzig - Blechschmidt M.A., Andreas; Lanzendorf, Martin; Wilde, Mathias (Raumforschung und Raumordnung, 2015)
Many cities in Germany are currently facing complex economic, ecological and social problems that cannot be resolved with traditional, departmentalized planning concepts. Integrated urban development concepts are therefore in high demand. However, the planning approaches associated with such integrated concepts hardly provide immediately applicable strategies. In this context, the paper discusses approaches for sustainable-mobility oriented urban development, using the German city of Leipzig as an example. Building on previous findings, the paper presents infrastructure-based concepts for advancing inner-city living, strengthening urban centres and promoting local mass transit. In addition, political, organizational and communicative courses of action will be demonstrated. Those measures include steps for improving the wider basic planning framework, concepts for strengthening inter- and intra-communal cooperation as well as integrated urban mobility concepts. The example of Leipzig shows clearly that infrastructure-based approaches are insufficient for sustainable-mobility oriented urban development. Rather, urban and transit planning needs to be much more attuned to the needs of the general public. This includes the integration of measures for mobility management with urban transit concepts. Finally, a political and legal framework focusing on sustainability goals, and a stronger consideration of regional links in urban planning are necessary for a more effective transformation of integrated urban development concepts.